2020
DOI: 10.1042/bsr20194012
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming off-targets: assessing Western blot signals for Bcnt/Cfdp1, a tentative component of the chromatin remodeling complex

Abstract: The Bucentaur (BCNT) protein family is characterized by a conserved amino acid sequence at the C-terminus (BCNT-C domain) and plays an essential role in gene expression and chromosomal maintenance in yeast and Drosophila. The mammalian Bucentaur/Craniofacial developmental protein 1 (Bcnt/Cfdp1) is also a tentative component of the SNF2-related CBP activator protein (Srcap) chromatin remodeling complex, but little is known about its properties, partly because few antibodies are available to examine the endogeno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Freshly cultured cells were subjected to protein extraction with RIPA (Beyotime, #P0013B) supplied with a proteinase inhibitor cocktail (Promega, #G6521). Western blot was performed as described previously [ 16 , 17 ]. The following primary antibodies were used: Anti-CRAD antibody (Sigma, #HPA043249) and anti-GAPDH antibody (Santa Cruz Biotechnology, #sc-32233).…”
Section: Methodsmentioning
confidence: 99%
“…Freshly cultured cells were subjected to protein extraction with RIPA (Beyotime, #P0013B) supplied with a proteinase inhibitor cocktail (Promega, #G6521). Western blot was performed as described previously [ 16 , 17 ]. The following primary antibodies were used: Anti-CRAD antibody (Sigma, #HPA043249) and anti-GAPDH antibody (Santa Cruz Biotechnology, #sc-32233).…”
Section: Methodsmentioning
confidence: 99%
“…The cfdp1 locus in zebrafish was initially misassigned to the RLTPR (RGD motif, leucine rich repeats, tropomodulin domain and proline-rich containing) gene and the role of BCNT/CFDP1 in the heart has not been investigated as yet. Thus, while there are sparse studies assessing the role of CFDP1, mainly in the chromatin remodeling complex via the maintenance of chromosome organization [23,24], its role in heart development and physiology remains to be addressed and evaluated, especially since GWAS studies have revealed the association of CFDP1 with CAD in humans [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse BCNT gene, cp27 was suggested to mediate early organogenesis and high level of its expression was demonstrated in developing mouse teeth, heart, lung and liver 1820 . Thus, while there are sparse studies accessing the role of cfdp1 in chromatin remodeling complex via the maintenance of chromosome organization 21,22 , little is known about not only its function and the mechanism it is involved in but also its role in heart physiology and morphogenesis. Recently, it was shown that the zebrafish gazami mutants carry a point mutation in the 3’ end of the gene, resulting in a truncated protein 23 .…”
Section: Introductionmentioning
confidence: 99%